Forseglet – spiselige dyr og flydende materialitet i et fødevarelaboratorium i København - Skjoldborg Brieghel, Signe (Slagmark - Tidsskrift for idéhistorie, 2019)
CONTAINED – EDIBLE ANIMALS AND FLUID MATERIALITY IN A FOOD LABORATORY IN COPENHAGEN In a small food laboratory in central Copenhagen, an attempt to make soy sauce from insects has resulted in a brownish liquid contained in a small bottle under a waxy seal. To the scientists who have made the liquid, edibility and the substances used to create it result from encounters between a number of different things. In recent times, however, global institutions such as the FAO have defined insects as a potential new food source in times of scarce resources and growing populations based on one thing in particular; their high yields of protein. I draw from my ethnographic fieldwork on practices of cooking with insects in the food laboratory to suggest that edibility, rather than a fixed quality of nutrition should be engaged as the result of an arduous work process situated amid ever-transforming divisions and connections. In times of calling upon ever more species to the canon of human industrial products, I argue, an important potential of ethnographic encounter lies in its abilities to raise questions of self-containment by bringing the muddles of collaboration to the fore of the discussion.